Correction: 3D aggregation of cells in packed microgel media. Issue 28 (8th July 2020) - Morley, Cameron D.; Tordoff, Jesse; O'Bryan, Christopher S.; Weiss, Ron; Angelini, Thomas E.
Abstract : Correction for '3D aggregation of cells in packed microgel media' by Cameron D. Morley et al., Soft Matter, 2020, DOI: ; 10.1039/d0sm00517g .